Caracterização fitofisionômica dos distritos de Camisão e Piraputanga, município de Aquidauana-MS - TAIANE REIS DE BRITO (2021)
The State of Mato Grosso do Sul is among the states with the greatest diversity, due to the presence of three biomes in its territory: Cerrado, Mata Atlântica e Pantanal. For the municipality of Aquidauana, the occurrence of two biomes is described, being Cerrado and Pantanal. This study aimed to carry out the phytophysiognomic characterization of vegetation fragments in the districts of Camisão and Piraputanga belonging to the municipality of Aquidauana, Mato Grosso do Sul. The surveys were carried out using the walking method, in the different physiognomies found, namely: cerrado, cerradão, gallery forest and semideciduous forest, in addition to anthropized areas. 97 species were identified, divided among 47 families, 20 species were not identified. The families with the highest number of species were Fabaceae, Bignoniaceae and Malvaceae, the first was present in all physiognomies as well as the species Guazumaulmifolia. The similarity was calculated between the physiognomies using the Jaccard index, where the only similar physiognomies were cerrado and gallery forest, with an index of 31%, sharing 23 species. It is necessary to continue floristic surveys for the area, since it is in priority areas for conservation